2020
DOI: 10.3390/v12080822
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B Lymphocytes Colonize the Respiratory Tract of Neonatal Mice and Modulate Immune Responses of Alveolar Macrophages to RSV Infection in IL-10-Dependant Manner

Abstract: Respiratory syncytial virus (RSV) is the prevalent pathogen of lower respiratory tract infections in children. The presence of neonatal regulatory B lymphocytes (nBreg) has been associated with a poor control of RSV infection in human newborns and with bronchiolitis severity. So far, little is known about how nBreg may contribute to neonatal immunopathology to RSV. We tracked nBreg in neonatal BALB/c mice and we investigated their impact on lung innate immunity, especially their crosstalk with alveolar macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…These Bregs are also not present in the adult lung, highlighting the importance of studying early-life immunity. A neonatal BALB/c mouse model of RSV-infection showed that Bregs colonise the lungs in the first week of life and can affect the overall respiratory immune environment [ 75 ]. These neonatal Bregs dampened the release of IFN-γ in response to RSV infection in an IL-10-dependent manner, resulting in a failure to contain RSV replication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These Bregs are also not present in the adult lung, highlighting the importance of studying early-life immunity. A neonatal BALB/c mouse model of RSV-infection showed that Bregs colonise the lungs in the first week of life and can affect the overall respiratory immune environment [ 75 ]. These neonatal Bregs dampened the release of IFN-γ in response to RSV infection in an IL-10-dependent manner, resulting in a failure to contain RSV replication.…”
Section: Resultsmentioning
confidence: 99%
“…This has been corroborated in human studies, where it was shown that these nBregs can be infected with human RSV (hRSV), and subsequently dampen the Type-1 immune response, promoting a biased Type-2 response and worsening disease outcomes [ 27 , 76 ]. An alternative method that has been proposed for nBregs to worsen RSV-associated pathogenesis is through the suppression of AMφ antiviral function [ 75 ]. The IL-10 produced by nBregs can suppress the secretion of IFN-α and -β ex vivo, influencing the AMφs towards a Type-17-like phenotype instead.…”
Section: Resultsmentioning
confidence: 99%
“…115 RSV model Breg cells produced IL−10 and reduce the expression of type-I interferon. 117 HIV patients have higher Breg frequencies. 116…”
Section: Viral Infectionsmentioning
confidence: 93%
“…After RSV infection, Breg cells produced IL-10 that can reduce the expression of type-I interferon secretion and thereby possibly reduce antiviral responses. 117 Besides viruses, bacterial infections can also trigger the induction of Breg cells. Helicobacter pylori infection is associated with an increased number of IL-10 + B cells.…”
Section: B Reg Cell Re S P On S E S During Infec Tionsmentioning
confidence: 99%
“…RSV particles bind and infect fetal Breg in lung tissues, inducing the upregulation of Breg CX3CR1 chemokine receptors that interact with RSV G glycoproteins to stimulate IL-10 secretion and downstream anti-inflammatory responses. 278,279 Profuse IL-10 release has been correlated with diminished T helper 1 (Th1) priming or activation. In conjunction with increased RSV-infected Breg cell frequencies, IL-10 elevations may be predictive for more severe outcomes in the setting of RSV infections during pregnancy.…”
Section: Pregnancyinfluencesonbcellresponsesto Viral Infectionsmentioning
confidence: 99%